Hubungan Antara Dukungan Sosial Dari Dosen Dengan Motivasi Menyelesaikan Skripsi Pada Mahasiswa - Didik Widiantoro; Sigit Nugroho; Yanwar Arief (Journal An-Nafs: Kajian Penelitian Psikologi, 2019)
The purpose of this research was to determine the correlation between lecturer’s social support with motivation in thesis completion of college students. The subjects in this study were 100 college. Sampling technique used purposive sampling technique. The research data were collected using (1) The scale of lecturer’s social support, and (2) motivation in thesis completion. Data analysis was performed with the technique of correlation analysis of Pearson Product Moment, with the help of a computer program SPSS 18 for windows. The results of the research,showed there was significant correlation between lecturer’s social support with motivation in thesis completion of college students. The higher lecturer’s social support, the higher motivation in thesis completion of college students and the lower lecturer’s social support, the lower motivation in thesis completion of college students. Indicated by the value of r=0, 398 and p=0,00 (p<0.01).